Erythropoietin’s Therapeutic Value in Preventing Methotrexate’s Adverse Renal Effects - A. Ali, Ali Hassan (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Methotrexate may cause problems with the kidneys. Nonetheless, erythropoietin’s advantageous extra-hematopoietic impact may protect against methotrexate-induced nephrotoxicity. Objectives: Clarifying the impact of renoprotective erythropoietin on renofunctional and renomorphological aspects in adult male albino rats will help determine its role in mitigating methotrexate-induced nephrotoxicity. Materials and Methods: 60 male albino rats were used in the investigation, and they were divided equally into 3 groups. The control one received normal saline 2 times a week for 9 weeks at a dosage of 0.5 mg/kg body weight (BW). Group 2 received 0.5 mg/kg BW intraperitoneal injections of methotrexate hydrate twice a week for 9 weeks. Group 3 received methotrexate hydrate intraperitoneally for the same amount of time and at the same dosage as group 2, along with a onceweekly subcutaneous injection (S.C) of 100 IU/kg recombinant human erythropoietin. Rats were slaughtered, renal sections were ready for histological analysis, and serum urea, creatinine, and albuminuria were determined at the conclusion of the study. Results: The methotrexate-treated group showed significantly higher levels of renal function assessed chemicals with worsening histological renal alterations when compared to the control or the methotrexate and erythropoietin co-treated group. The latter showed significantly improved microscopic renal alterations along with statistically significant reductions in the drug levels. Furthermore, there were negligible statistical differences in renal morphology and biochemistry between different groups. Conclusion: This study found that animals given with erythropoietin in addition to methotrexate provided a valuable and effective resistance against methotrexate-induced nephrotoxicity.